Föreställningar om stadsomvandlingens Kiruna - Sjöholm, Jennie (Göteborg : Institutionen för kulturvård, Göteborgs universitet, 2010)
The city of Kiruna is about to transform, due to the expansion of the iron ore mine that is dominating the city’s labour market. The built environment is at the same time a cultural heritage of national interest. The purpose of this paper is to examine which images of the city that become important due to the city transformation. This is accomplished by a textual criticism of three different sources; newspaper articles, the municipality’s plans and documents, together with a survey made at the local high school. Places mentioned in the source material have been mapped, and then interpreted as being imaginary geographies of the images of Kiruna. Three strong images have been identified. These are Kiruna as the Mining City, as the Ideal City, and as the City That Will Move. Different sets of places are connected to each image. Apart from these places, there are an other kind of places, important to the everyday life in Kiruna. All together, these places constitutes Kiruna. However, in the paper they are explained as being different means of the production of space. Using Henri Lefebvres terms, the images are an example of representational spaces, while the everyday life is a spatial practice. This helps explaining why the built environment is perceived in different ways, and why certain places are looked upon as cultural heritage. Upprättat; 2010; 20110620 (jensjo)